Environmental impact assessment in Brazil - Fowler, Harold G. [UNESP]; De Aguiar, Ana Maria Dias [UNESP] (Elsevier, 1993)
Brazilian environmental impact assessment (EIA) had a relatively late birth and is still far from being operative by international standards. Currently, geological, economic, and social considerations are more highly valued. Nevertheless, EIA has become important in shaping governmental environmental policy. The state of São Paulo is responsible for 40% of all EIAs produced in Brazil, and the number of EIAs produced is proportional to state population density.
Keywords: developing country; environmental impact assessment; government policy; policy instrument; project planning; Brazil